2008
DOI: 10.1016/j.clon.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Did the Pattern of Practice in the Prescription of Palliative Radiotherapy for the Treatment of Uncomplicated Bone Metastases Change between 1999 and 2005 at the Rapid Response Radiotherapy Program?

Abstract: Between 1999 and 2005, the use of single-fraction radiotherapy increased, corresponding to publications showing equal efficacy of pain relief between single and multiple fractions in the management of uncomplicated bone metastases. However, about a third of patients still received multiple fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…Radiation oncologists certified from 1990 onward were more likely to prescribe multiple fractions of radiation therapy to patients, which accords with the findings of the previous rrrp study 29 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Radiation oncologists certified from 1990 onward were more likely to prescribe multiple fractions of radiation therapy to patients, which accords with the findings of the previous rrrp study 29 .…”
Section: Discussionsupporting
confidence: 81%
“…Our previous study of the rrrp between 1999 and 2005 revealed that in 65% of palliative radiation therapy cases, a single fraction was prescribed, and that in 35%, multiple fractions were prescribed 29 , findings identical to those in the present study. Furthermore, in both time periods, a single fraction was more likely to be prescribed for patients with a prostate cancer primary or for older patients, and by radiation oncologists with a greater number of years of certification for independent practice.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In view of the accuracy of delivery and the amount of dose delivered in a single fraction, the Gamma Knife device is an excellent option for treating these patients. Several studies [2,3] have shown that an 8 Gy dose is as effective as other schedules with the same side effects. So we decided to use an 8 Gy marginal dose, so the maximal dose was higher (17.77 Gy).…”
Section: Discussionmentioning
confidence: 97%
“…[37][38][39] Single fractions are more convenient for people, can reduce the strain on radiotherapy resources, and are increasingly being used in other jurisdictions. 40 While in Nova Scotia multiple fractions were commonly used during the time period of this study, the Halifax treatment site has been exploring the implementation of rapid response radiotherapy to provide therapy soon after referral and streamline the process, minimizing the number of PRT clinic visits necessary to deliver treatment. When appropriate, the aim is to have consultation, treatment planning and the initiation of treatment all in one visit.…”
Section: Other Strategies To Improve Accessmentioning
confidence: 99%